Is There an Enabling Environment for Nutrition-Sensitive Agriculture in South Asia? Stakeholder Perspectives from India, Bangladesh, and Pakistan. Issue 2 (June 2015) - van den Bold, Mara; Kohli, Neha; Gillespie, Stuart; Zuberi, Samar; Rajeesh, Sangeetha; Chakraborty, Barnali
Background: Almost half of all children in South Asia are stunted. Although agriculture has the potential to be a strong driver of undernutrition reduction and serves as the main source of livelihood for over half of South Asia's population, its potential to reduce undernutrition is currently not being realized. Objective: The Leveraging Agriculture for Nutrition in South Asia (LANSA) research consortium seeks to understand how agriculture and agrifood systems can be better designed to improve nutrition in South Asia. In 2013 and 2014, LANSA carried out interviews with stakeholders influential in, and/or knowledgeable of, agriculture–nutrition policy in India, Pakistan, and Bangladesh, to gain a better understanding of the institutional and political factors surrounding the nutrition sensitivity of agriculture in the region. Methods: Semistructured interviews were carried out in India, Bangladesh, and Pakistan with a total of 56 stakeholders representing international organizations, research, government, civil society, donors, and the private sector. Results: The findings point to mixed perspectives on countries' policy sensitivity toward nutrition. There was consensus among stakeholders on the importance of political commitment to nutrition, improving nutrition literacy, strengthening capacities, and improving the use of financial resources. Conclusions: Although there are different ways in which South Asian agriculture can improve its impact on nutrition, sensitizing key influencers to the importance of nutrition for the health of a country's population appears as a critical issue. This should in turn serve as the premise for political commitment, intersectoral coordination to implement nutrition-relevant policies, adequately resourced nutrition-specific and nutrition-sensitive programs, and sufficient capacities at all levels.